A link between phenotypic robustness and life expectancy in Drosophila melanogaster - L. P. Zakharenko; D. V. Petrovskii; I. G. Dranov; S. A. Fedorova; N. S. Yudin; A. V. Pindyurin; Y. M. Moshkin (Вавиловский журнал генетики и селекции)
Long-lived systems are expected to be stable, i. e. resistant to either external influences, or internal failures. Robustness of biological systems can be defined as a reciprocal value to their phenotypic plasticity expressed through a coefficient of variation (C.V.) for positively distributed phenotypic traits. Considering lifespan as phenotype, which integrates all functions of an organism, we showed that its phenotypic robustness correlates positively with life expectancy. We assessed lifespan parameters for a selection of inbred Drosophila melanogaster strains from Drosophila Genetic Reference Panel (DGRP) reared at 29 ºС. The robustness of lifespan phenotype (C.V.–1) correlated positively with estimated life expectancy for these strains. The same relation also holds for the lifespan of all DGRP strains reared at 25 ºС. Also, in agreement with previous observations, upon temperature change (decrease or increase) the survival curves scaled in time (stretched or shrunk respectively). In other words, the average lifespan decreased for flies reared at elevated temperature, but so did the standard deviation, and thus the coefficients of variation remained in the same range. From this we conclude that coefficients of variation correlate with life expectancies and account for the robustness of lifespan phenotype irrespective of accelerated aging caused by temperature.